2011
DOI: 10.1073/pnas.1110439108
|View full text |Cite
|
Sign up to set email alerts
|

Niemann–Pick type C 1 function requires lumenal domain residues that mediate cholesterol-dependent NPC2 binding

Abstract: Niemann-Pick type C1 (NPC1) protein is needed for cellular utilization of low-density lipoprotein-derived cholesterol that has been delivered to lysosomes. The protein has 13 transmembrane domains, three large lumenal domains, and a cytoplasmic tail. NPC1's lumenally oriented, N-terminal domain binds cholesterol and has been proposed to receive cholesterol from NPC2 protein as part of the process by which cholesterol is exported from lysosomes into the cytosol. Using surface plasmon resonance and affinity chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
175
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(183 citation statements)
references
References 22 publications
7
175
0
1
Order By: Relevance
“…The functions of the NTD and the MLD have been well established by previous studies (18,30,31). Our higher resolution data revealed several hitherto unknown contacts between the CTD and NTD domains of NPC1 and allowed an atomic model for mapping NPC-causing mutations.…”
Section: Discussionsupporting
confidence: 78%
“…The functions of the NTD and the MLD have been well established by previous studies (18,30,31). Our higher resolution data revealed several hitherto unknown contacts between the CTD and NTD domains of NPC1 and allowed an atomic model for mapping NPC-causing mutations.…”
Section: Discussionsupporting
confidence: 78%
“…The NPC2-NPC1 MLD complex structure explains the previously reported cholesterol dependence of this interaction (8).…”
Section: Resultssupporting
confidence: 69%
“…These data support a "hydrophobic hand-off" transfer model in which NPC2 binds cholesterol in the lysosome lumen and then binds to NPC1 to deliver cholesterol to NPC1's NTD; transfer of NTD-bound cholesterol to NPC1's transmembrane domain follows, to achieve sterol export from lysosomes (14). Also supporting this transfer model was our finding that NPC2-bearing cholesterol can bind to NPC1's MLD at acidic pH (8). The presence of a conserved, "sterol-sensing" domain within NPC1's membrane spanning portions has implicated these sequences as possible sterol acceptors (15,16).…”
supporting
confidence: 76%
“…The capped form may represent an inactive state of NPC1 protein because surface residues needed for interaction with NPC2 (and Ebola virus) are shielded by the presence of the N-terminal domain. Nevertheless, both the N-terminal domain and lumenal domain 2 are likely to interface with NPC2 as part of the cholesterol transfer process (12,13,20). Both the cryo-EM and crystal structures highlight the unusual height of the protein in relation to the lysosome's internal limiting membrane (5,20).…”
mentioning
confidence: 99%
“…Although this model is very attractive, a direct interaction between the NPC1 N-terminal domain and NPC2 protein has not been detected to date. Using an engineered, soluble construct, Deffieu and Pfeffer (13) showed that NPC1's second lumenal domain binds NPC2 directly, but only at the low pH seen in endosomes and lysosomes and only when it carries cholesterol (13). Thus, the second domain of NPC1 might hold onto NPC2 to facilitate cholesterol transfer from NPC2 to the NPC1 N-terminal domain.…”
mentioning
confidence: 99%